2018
DOI: 10.1128/aac.01828-17
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplex DNA Motifs in the Malaria Parasite Plasmodium falciparum and Their Potential as Novel Antimalarial Drug Targets

Abstract: G-quadruplexes are DNA or RNA secondary structures that can be formed from guanine-rich nucleic acids. These four-stranded structures, composed of stacked quartets of guanine bases, can be highly stable and have been demonstrated to occurin vivoin the DNA of human cells and other systems, where they play important biological roles, influencing processes such as telomere maintenance, DNA replication and transcription, or, in the case of RNA G-quadruplexes, RNA translation and processing. We report for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 50 publications
(70 reference statements)
3
76
0
Order By: Relevance
“…Effect of NMM on infectious agents. NMM has been identified as a potential drug against the malaria parasite [75], the pseudorabies virus [71], and antigenic variation in the gonorrhea bacterium [76]. These effects are directly linked to NMM's ability to induce and stabilize GQ structures, thereby indicating that GQs are viable targets in infectious diseases.…”
Section: Using Nmm To Study Gq Dna In Biological Contextsmentioning
confidence: 99%
“…Effect of NMM on infectious agents. NMM has been identified as a potential drug against the malaria parasite [75], the pseudorabies virus [71], and antigenic variation in the gonorrhea bacterium [76]. These effects are directly linked to NMM's ability to induce and stabilize GQ structures, thereby indicating that GQs are viable targets in infectious diseases.…”
Section: Using Nmm To Study Gq Dna In Biological Contextsmentioning
confidence: 99%
“…G-quadruplex sequences are also evolutionary conserved across different living organisms. They are present in essential genomic loci of Saccharomyces cerevisiae 13,14 , Plasmodium falciparum 15,16 , Neiserria gonorrhea 17 , Mycobacterium tuberculosis 18 , Streptococcus pneumononiae 19 and several viruses 20 . They are also found in the genomes of plants including Arabidopsis thaliana, and Oryza sativa 21,22 .…”
mentioning
confidence: 99%
“…Very few Plasmodium sequences have been thus verified, and the two that have were selected a priori by QGRS Mapper. (Notably, neither of them -belonging to the rifin gene PF3D7_0700200 and the var upsB region [15,29] -were found here by G4 Hunter: they presumably fall into the false negative category which is expected to be quite large at a threshold of 1.7.) Here, we experimentally tested three new G4 Hunter motifs, including two with the apparent potential to form only two-quartet rather than three-quartet G4s.…”
Section: Discussionmentioning
confidence: 62%
“…This could potentially allow the var genes to benefit from the recombination-promoting effects of G4s without suffering any interruption of coding-strand transcription, which could impede efficient production of PfEMP1. (We have previously showed that a stabilized coding-strand G4 can inhibit transcription of a rifin reporter gene [29], so the same could be true for G4-encoding var genes.) Coding PQSs -at least amongst the upsB var genes that were analysed in figure 5 -occurred mostly around the middle of var gene sequences, within the second exon that encodes the variable extracellular domain of PfEMP1.…”
Section: Discussionmentioning
confidence: 86%